identité du mois de juin 2014

Posté le : mercredi 4 juin 2014 par Vincent Thill
[(27t^2+s^2)^2(s^2+3t^2)^2-(27t^3-s^3+ts^2-3st^2)^2(s-3t)^2]^4 + [2(s^2+3t^2)(27t^3-s^3+ts^2-3st^2)(27t^2+s^2)(s-3t)]^4 + [(27t^2+s^2)^2(s^2+3t^2)^2+(-27t^3-s^3-ts^2-3st^2)^2(s+3t)^2)]^4 =

 

[(27t^2+s^2)^2(s^2+3t^2)^2-(-27t^3-s^3-ts^2-3st^2)^2(s+3t)^2]^4 + [2(s^2+3t^2)(-27t^3-s^3-ts^2-3st^2)(27t^2+s^2)(s+3t)]^4 + [(27t^2+s^2)^2(s^2+3t^2)^2+(27t^3-s^3+ts^2-3st^2)^2(s-3t)^2]^4

exemple    s = 2   et    t = 3                 pgcd = 2

(18019320)^4+(-36393721)^4+(68325769)^4= (-9696120)^4+(-67634281)^4+(40610329)^4

équation du type A^4+B^4+Z^4=X^4+Y^4+C^4

avec  ( A )( B )  = ( X )( Y )    et    A² + B² = C²    et    X² + Y² = Z²

Les commentaires sont fermés